SOCIAL MEDIA AND THEIR ROLE IN THE EDUCATIONAL PROCESS (YOU TUBE SITE) IS A MODEL - Ammar Ibrahim Mohammed Al-Yasr; Adnan Kazem Amansef (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Educational space has opened up on technology extensively, social media has become a modern, interactive pedagogy, and you Tube is a social media platform that includes teaching and educational lessons in its traditional, classical and modern form based on drama, kinesthetic performance, competition programs and more. The first chapter included the goal of research, problem, importance, and borders, while the second chapter included three mabahith, the first under the title "Social Media .. The skills, terminology and development, the second under the heading Technical and esthetic building of the video scenes displayed on you Tube and the third under the heading "you Tube") in the educational process, while the third chapter includes the research methodology, society, its equipment, and its practical procedures, and chapter 4 contains conclusions, conclusions and recommendations.